INDIA'S COLLABORATION IN SCIENCE AND TECHNOLOGY WITH SOUTH EAST ASIAN COUNTRIES - B.M., Gupta; Kashmiri, Lal; A.N., Zainab (Malaysian Journal of Library and Information Science, 2017)
The collaboration in science and technology (S&T) is fast emerging in the scientific world. India recognized the importance of international scientific collaboration in S&T quite early and has signed a number of S&T agreements with South East Asian countries. In this paper, the collaboration is presented through the analysis of co-authored research papers published during the period 1996 to 2000 in the journals covered by the Science Citation Index. The study covers the nature and the areas of S&T collaborations, institutions involved, and the impact of these collaborations on their individual fields. It is revealed that a total of 329 co-authored papers were published during the period. Out of these, 214 were published through bilateral and 115 through multilateral efforts. The priority areas vary with the nature of collaboration as well as with the collaborating country. The institutions involved in these collaborations are also indicated. The research papers analyzed reflect the present status of India’s collaboration in S&T with the South East Asian countries. Such a study will help decision-makers to identify the potential S&T areas for future international cooperation.